1997
DOI: 10.2307/146219
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Quality in Child Care Centers

Abstract: Abstract-We use data from a sample of child care centers to estimate the relationships between cost and child care quality, and between revenue and quality. We use a measure of child care quality, designed by developmental psychologists, that is positively associated with child development. Taking the estimated cost-quality and revenue-quality relationships as given, we estimate the objective functions of firms and compute the quality supply function. The results indicate that the supply of quality is moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 32 publications
(21 reference statements)
4
41
0
1
Order By: Relevance
“…Others noted that when they started teaching, challenges arose for which they felt unprepared. Such responses support previous research that has found that the effects of training sessions on program quality tend to fade over time (Blau 1997;Clarke-Stewart et al 2002). By the middle of Year One, therefore, ongoing training schedules had been implemented in all CORAL cities.…”
Section: The Continuous Program Quality Improvement Cyclesupporting
confidence: 85%
See 2 more Smart Citations
“…Others noted that when they started teaching, challenges arose for which they felt unprepared. Such responses support previous research that has found that the effects of training sessions on program quality tend to fade over time (Blau 1997;Clarke-Stewart et al 2002). By the middle of Year One, therefore, ongoing training schedules had been implemented in all CORAL cities.…”
Section: The Continuous Program Quality Improvement Cyclesupporting
confidence: 85%
“…The CORAL sites' experiences showed that this traditional approach to staff development was ineffective at creating lasting change. This experience mirrors research findings reviewed in the introduction that common approaches to staff development, such as one-time demonstrations of new curricula and informal monitoring of staff progress, rarely make lasting Note: There were fewer groups to observe in Year Two because fewer of these ''year older'' youth participated and the sites organized participants into fewer groups for activities ** p \ .01, *** p \ .001 a The percent of observations during which each literacy strategy was observed b Significance levels noted in the Year Two column signify where change from 1 year to the next was significantly different c Because vocabulary development strategies could be observed in tandem with any other literacy strategy, it was not marked as absent or present at any given time but was only rated on the scale of 1-5; thus, only an average rating for this strategy is available impacts on staff members' skill development or program quality (Blau 1997;Clarke-Stewart et al 2002;DuBois et al 2002). Improvements in programming quality were achieved when more continuous and ongoing efforts at quality improvement strategies were employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models assume a single input to the production of the quality of the service, so regulating the input is equivalent to regulating quality. There are many inputs to the production of quality in child care, and evidence suggests that input substitution is technically feasible (Blau, 1997(Blau, , 2000. Thus the effect of a regulation that requires an increase in the quantity of one input, such as trained teachers, might be offset to some extent by changes in other inputs that are not regulated, such as group size in some states.…”
Section: Predictions From Economic Theorymentioning
confidence: 99%
“…A notable exception to the prevailing wisdom on child-to-staff ratios is Blau (1997), who studied the effects of ratios (and other variables) on teacher behavior, activities, and classroom environment in five cities. When he applied OLS regression techniques, he found that child-to-staff ratios had the expected positive effects; however, when he utilized a fixed effects model that controlled for unobserved differences in center characteristics, he found that those positive effects all but disappeared (only the effects of a lower child-to-staff ratio on the classroom environment remained statistically significant and positive).…”
Section: Child Care Qualitymentioning
confidence: 99%